‘Is she? Or, a little detour, dragged by the ear’ - Cyrino, Marina Pereira (Revista Brasileira de Estudos da Presença, 2022)
This article starts from an account of the process of commissioning, composing, and performing Mansoor Hosseini’s Casss...andra (2015), a solo work for flute collaboratively composed. By invoking the mythic figure of Cassandra, following her transformations through centuries of Western Art and her transformations through the researcher’s own body, this article invites the reader for possible ways of escaping the exotification of Cassandra as the mad sorceress, the female stranger. By weaving together artistic research, creative practices, and personal narrative, the entanglement of Cassandra, with Casss…andra, with the song of the flute, reframe and reclaim the auditory dimension of Cassandra’s gift.